PENGUKURAN REKAHAN, PADA BATUAN SEDIMEN DI SUNGAI CIPOGO PADALARANG KABUPATEN BANDUNG JAWA BARAT - Rafiqah Indah Sari; Rexy Elnando; Nurfajri Indra; Gina Rahayu; Sildila Sari; Mufti Khairatunnisa; Ronal Wilnika; Devi L Maria; Reza Nofri Andika; Muhammad Noval; Dian Adhetya Arif (JURNAL BUANA, 2020)
Rock is a solid substance that contains minerals and is formed naturally. Joint is a fractured plane without a shift in the rock body and can be present systematically formed by tectonic forces and can be analyzed as an interpretation of its forming tectonic forces from systematic data. This research was conducted in Sugai Cibogo, Padalarang, West Bandung Regency, with coordinates 06049'29.07 " S and 107026'17,69 "S. This type of research used in research is a quantitative descriptive study by telling the conditions of the field conditions as is. The purpose of this study was to determine the direction of rock fractures in the Cibogo Padalarang river and how to take samples in the Cibogo Padalang river. The results of this study found that the fracture that occurred was a normal fault because sigma 1 was bigger than the other sigma and the sample was taken using a geoglogic hammer, compass, meter by determining the age of rocks and others.